Impact of environmental factors on heart failure decompensations. (4th September 2019) - Escolar, Vanessa; Lozano, Ainara; Larburu, Nekane; Kerexeta, Jon; Álvarez, Roberto; Juez, Benjamín; Echebarria, Amaia; Azcona, Alberto; Artola, Garazi
Abstract: Aims: Heart failure (HF) is a clinical syndrome caused by a structural and/or functional cardiac abnormality, resulting in a reduced cardiac output and/or elevated intracardiac pressures at rest or during stress. This disease often causes decompensations, which may lead to hospital admissions, deteriorating patients' quality of life and causing an increment on the healthcare cost. Environmental exposure is an important but underappreciated risk factor contributing to the development and severity of cardiovascular diseases, such as HF. Methods and results: We used two different sets of data (January 2012 to August 2017): one related to the number of hospital admissions and the other one related to the environmental factors (weather and air quality). Admissions related data were grouped in weeks, and then two different studies were performed: (i) a univariate regression to determine whether the admissions may influence future hospitalizations prediction and (ii) a multivariate regression to determine the impact of environmental factors on admission rates. A total number of 8338 hospitalizations of 5343 different patients are available in this dataset, with a mean of 4.02 admissions per day. In European warm period (from June to October), there are significant less admissions than that in the cold period (from December to March), with a clear seasonality of admissions, because there is a similar pattern every year. Air temperature is the most significant environmental factor ( r = −0.3794, P < 0.001) related to HF hospital admissions, showing an inversed correlation. Some other attributes, such as precipitation ( r = 0.0795, P = 0.05), along with SO2 (precursor of acid rain) ( r = 0.2692, P < 0.001) and NOX air (major air pollutant formed by combustion systems and motor vehicles) ( r = 0.2196, P < 0.001) quality parameters, are also relevant. Humidity and PM10 parameters do not have significant correlations in this study ( r = 0.0469 and r = − 0.0485 respectively), neither relevant P ‐values ( P = 0.238 and P = 0.324, respectively). Conclusions: Several environmental factors, such as weather temperature and precipitation, and major air pollutants, such as SO2 and NOX air, have an impact on the HF‐related hospital admissions rate and, hence, on HF decompensations and patient's quality of life.